Innovation and scientific activity as factors in managing the organisations and territories’ sustainable development - P. A. Kostromi (Ekonomika Nauki)
This study compares national scientific and innovation indicators with the sustainable development management goals of organizations and territories. Its purpose is to determine the extent to which indicators of scientific progress, innovation development, and the innovative economy align with the Sustainable Development Goals (SDGs) adopted by the UN General Assembly in 2015. The Global Innovation Index (GII), compiled annually by the World Intellectual Property Organization (WIPO), serves as the primary data source.Noting Russia’s gradual decline in the GII rankings, the author emphasizes the critical importance of defining the role of science and innovation in achieving balanced socio-economic and environmental sustainability at macro, meso, and micro levels. The information and methodological framework draws on an analysis of Russian regulations governing innovation processes, alongside data from WIPO and the United Nations.Key findings identify: (1) the types of innovation exerting the strongest and weakest influence on sustainable development management processes for organizations and territories; (2) the distinct roles of the innovation environment, social innovations, economic innovations, and ecological innovations in fostering balanced sustainable development for economic entities; and (3) specific sustainable development management objectives that are either omitted or inadequately reflected in the indicators used to assess scientific and innovation progress at national, sectoral, and corporate levels.